Salivary levels of suPAR, HIF-1α and TNF-α in different grades of stage III periodontitis - İsmail Taşdemir; Özgür Özgören; Huriye Erbak Yılmaz; Emine Kartal; Şeyma Altunyaprak; Mehmet Sağlam (BMC Oral Health)
Abstract Background The aim of the study is to evaluate saliva levels of Soluble urokinase plasminogen activator receptor (suPAR), Hypoxia-inducible factor-1 alpha (HIF-1α) and tumor necrosis factor-alpha (TNF-α) in stage III grade A, grade B, grade C periodontitis and periodontal health and to understand the roles of these molecules in periodontal inflammation process and also to compare the three biomarkers' discriminative efficacy in periodontal disease. Methods A total of 80 individuals, 20 with stage III grade A periodontitis (group A), 20 with stage III grade B periodontitis (group B), 20 with stage III grade C periodontitis (group C) and 20 with healthy periodontium (group H) were recruited for this study. Full-mouth clinical periodontal measurements were recorded in periodontal charts. Whole saliva samples were collected to determine the levels of suPAR, HIF-1α and TNF-α in study groups using enzyme-linked immunosorbent assay (ELISA) method. Results The saliva concentration of suPAR, HIF-1α, and TNF α was significantly higher in group A, group B, and group C compared with group H (p < .05). Additionally, salivary suPAR concentration was significantly higher in group C than in groups A and B (p < .05). Positive statistically significant correlations were observed between three biomarkers and all clinical parameters (p < .05). Conclusions Increased levels of saliva suPAR, HIF-1α, and TNF α suggest that these molecules may play a role in periodontitis. In addition, the higher salivary suPAR levels in grade C periodontitis compared to other grades suggest that suPAR may be one of the potential molecules that can be used to predict disease progression and periodontal disease classification. Trial registration Before starting the study, the study plan was uploaded to clinicaltrials.gov.tr ​​and an identification number was obtained (Date: 21.05.2024, İdentification number: NCT06430450).